HUBUNGAN TINGKAT PENDIDIKAN ORANG TUA DENGAN PERSEPSI PEMBELAJARAN CALISTUNG DI TAMAN KANAK-KANAK SE-KECAMATAN PADANG UTARA KOTA PADANG - Wahyu Dwi Rahma; Yaswinda; Dadan Suryana; Setiyo Utoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning to read, write, and count (calistung) in kindergarten remains a topic that raises various perceptions among parents. Parents' education level is presumed to be one of the factors influencing this perception. This study aimed to determine the relationship between parents' education level and their perception of calistung learning in kindergartens in North Padang Subdistrict, Padang City. This quantitative correlational study involved 90 parents selected through cluster random sampling from a population of 866 parents across 24 kindergartens. Data were collected using a questionnaire and analyzed using descriptive and inferential statistics. Because the data on parents' perception were not normally distributed (Kolmogorov-Smirnov, Sig. = 0.000 < 0.05), hypothesis testing was conducted using Spearman Rank correlation. The results showed a correlation coefficient of 0.075 with a significance value of 0.480 (p > 0.05), indicating a positive but very weak and statistically non-significant relationship between parents' education level and their perception of calistung learning. Therefore, the research hypothesis was rejected. Additional descriptive findings showed that parents' positive attitudes and participation in school activities were consistently high across all education levels. These findings suggest that parents' perception of calistung learning is shaped more by attitude and engagement than by formal education level alone.